Explores the Relationship between Organizational Culture and Organizational Performance in the Bangladeshi Microfinance Sector: Organizational Innovation is a Mediating Factor - Akhter, Parul; Chaity, Naznin Sultana (European Scientific Journal, ESJ, 2024)
The purpose of this study is to explore the relationship between organizational culture and organizational performance, whereas organizational innovation focuses as a mediating variable in the microfinance organization in Bangladesh. The current study looks at the relationships between organizational culture, organizational performance, and organizational innovation plays mediating factor role. The study used a self-administered questionnaire using a five-point Likert scale. The data were collected from 300 middle and senior managers and considered top fifty microfinance organizations in Bangladesh. The hypotheses and connections between the constructs were empirically tested using structural equation modeling (SEM) along with the partial least squares (PLS) approach. The findings indicate that organizational culture is favorably and significantly related to organizational innovation and firm performance. Organizational innovation has a strong positive impact on organizational performance. Organizational innovation, on the other hand, mediates the indirect relationship between organizational culture and organizational performance. The study’s findings indicate that executives and policy-developers should focus on business culture and organizational innovation in addition for increasing efficiency and maintaining a competitive advantage.